Bridging the sanitation gap between disaster relief and development. Issue 4 (5th March 2015) - Lai, Ka‐Man; Ramirez, Claudia; Liu, Weilong; Kirilova, Darina; Vick, David; Mari, Joe; Smith, Rachel; Lam, Ho‐Yin; Ostovari, Afshin; Shibakawa, Akifumi; Liu, Yang; Samant, Sidharth; et al.
<x xml:space="preserve">Abstract</x> By interpreting disasters as opportunities to initiate the fulfilment of development needs, realise the vulnerability of the affected community and environment, and extend the legacy of relief funds and effort, this paper builds upon the concept linking relief, rehabilitation and development (LRRD) in the sanitation sector. It aims to use a composite of case studies to devise a framework for a semi‐hypothetical scenario to identify critical components and generic processes for a LRRD action plan. The scenario is based on a latrine wetland sanitation system in a Muslim community. Several sub‐frameworks are developed: (i) latrine design; (ii) assessment of human waste treatment; (iii) connective sanitation promotion strategy; and (iv) ecological systems and environmental services for sanitation and development. This scenario illustrates the complex issues involved in LRRD in sanitation work and provides technical notes and references for a legacy plan for disaster relief and development.